Patterns of food preparation in children and adult diets and their associations with demographic and socio-economic characteristics, health and nutritional status, physical activity, and diet quality - Rei, MCC (2025)
This cross-sectional study aimed to identify patterns of food preparation and examine their demographic and socio-economic drivers, along with impacts on health and nutritional status, physical activity, and diet quality. Dietary data from a national-representative sample (n = 5005, 3-84 years) of the Portuguese National Food, Nutrition, and Physical Activity Survey (IAN-AF 2015/16) were classified by preparation locations (at or away from home) and analysed via hierarchical clustering. Logistic regression models were used to examine associations between demographic and socio-economic factors and food preparation patterns and between these patterns and health and nutritional status, physical activity, and diet quality. The most common food preparation pattern (followed by 45.4% of participants) represented the highest intake of foods prepared by away-from-home establishments. Adolescents (vs. children, OR = 0.29, 95%CI = 0.17, 0.49) and older adults (vs. adults, OR = 0.37, 95%CI = 0.26, 0.53) had lower odds of following this pattern, whereas adult men (vs. women, OR = 4.20, 95%CI = 3.17, 5.57) had higher odds. Higher education, higher household income, and having children/adolescents in the household also increased the odds of eating foods prepared away from home, whereas living in rural areas or in food-insecure households decreased the odds. Noticeably, adults consuming more foods prepared away from home had lower odds of being overweight or obese (OR = 0.74, 95%CI = 0.56, 0.97), but higher odds of sedentarism (OR = 1.45, 95%CI = 1.08, 1.96) and poor diet (OR = 3.01, 95%CI = 2.08, 4.34) compared to those consuming more foods prepared at home by themselves. Dietary patterns marked by high away-from-home food preparation prevail. While these correlated with higher socio-economic status, sedentarism, and poorer diet - relatively to patterns with greater reliance on homecooked food - they were not linked to higher odds of obesity. © The Author(s), 2025.